Brain-reactive lymphocytotoxic antibodies in the serum of patients with systemic lupus erythematosus. - Bluestein, H G (1976)
Homogenized tissue from the frontal cortex of normal human brains obtained at postmortem examination was used to absorb lymphocytotoxic antibody from the serum of six patients with systemic lupus erythematosus (SLE). Four absorptions of all of the SLE sera with equal volumes of homogenized brain tissue at 4 degrees C depleted their cytotoxic capacity more than 90%. Three of the six sera, however, retained some lymphocytotoxicity despite extensive brain absorption. Absorbed lymphocytotoxic antibodies were eluted from brain tissue absorbents at 37 degrees C. Cytotoxicity of the brain eluates was blocked by antibodies to human IgM (mu-chain specific) but not anti-IgG. The unabsorbed SLE sera, brain-absorbed sera, and brain eluates were equally cytotoxic to T (thymus-derived) and B (bone marrow-derived) cells fractionated from normal human peripheral blood lymphocytes. Thus, the lymphocytotoxic antibodies in SLE serum exhibit no preference for circulating human T cells. An analysis of the clinical records of 40 patients with SLE whose serum cytotoxic capacity had been determined revealed that circulating lymphocytotoxicity is greater in sera of patients with central nervous system (CNS) manifestations than in other SLE patients. This observation suggests a possible role for brain-reactive lymphocytotoxic antibodies in the development of CNS disease in SLE.